2012
DOI: 10.1128/aem.01144-12
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Physicochemical Characterization of Small-Scale Cocoa Fermentations and Screening of Yeast and Bacterial Strains To Develop a Defined Starter Culture

Abstract: Spontaneous cocoa bean fermentations performed under bench-and pilot-scale conditions were studied using an integrated microbiological approach with culture-dependent and culture-independent techniques, as well as analyses of target metabolites from both cocoa pulp and cotyledons. Both fermentation ecosystems reached equilibrium through a two-phase process, starting with the simultaneous growth of the yeasts (with Saccharomyces cerevisiae as the dominant species) and lactic acid bacteria (LAB) (Lactobacillus f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
135
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(148 citation statements)
references
References 35 publications
6
135
1
6
Order By: Relevance
“…Batista et al (2015) also showed this species to have a similarly low population (around 3 Log cell/g) during spontaneous fermentation process. Researchers from Brazil have also found similar species in cocoa fermentation (Moreira et al 2013;Pereira et al 2012;Ramos et al 2014;Schwan and Wheals 2004).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Batista et al (2015) also showed this species to have a similarly low population (around 3 Log cell/g) during spontaneous fermentation process. Researchers from Brazil have also found similar species in cocoa fermentation (Moreira et al 2013;Pereira et al 2012;Ramos et al 2014;Schwan and Wheals 2004).…”
Section: Discussionmentioning
confidence: 94%
“…Species belonging to the genera Acetobacter and Gluconobacter have been described in different cocoa fermentations (Ardhana and Fleet 2003;Garcia-Armisen et al 2010;Lima et al 2011;Moreira et al 2013;Pereira et al 2012;Ramos et al 2014;Schwan and Wheals 2004). The species A. pastorianus and G. oxydans were detected by PCR-DGGE during both fermentations.…”
Section: Discussionmentioning
confidence: 98%
“…The yeast P. kudriavzevii has been isolated from different food fruit sources, such as cocoa beans, as the strain used in the present work (Pereira et al 2012). This yeast has a biotechnological potential for bio-ethanol (Dhaliwal et al 2011) production, in agriculture practices as bio fertilizer (Chan et al 2012) or in the bioremediation of heavy metals (Ubeda et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Among the 155 strains, 26 (16.77%) were Acetobacter genus. were able to oxidize acetic acid and O indicated by turning of medium This observation was not the same observation has been regularly recorded in cocoa beans fermentation [8,14].…”
Section: Total Of Isolates Mal Lac Galmentioning
confidence: 66%
“…This microbial activity generates a range of metabolites end-products such as alcohols and organic acids which diffuse into beans to cause their death. The change triggers an array of biochemical reactions and chemical changes within the beans, that are essential for the development of the characteristic cocoa flavour [12,13,14].…”
Section: Introductionmentioning
confidence: 99%